Experimental Research on Heat Pump Heating Performance at Low Temperature for Electric Vehicles - Yang Zhongcheng; Su Lin; Yu Rong; Fang Yidong; Li Kang; Mu Wenjie (Zhileng xuebao)
To investigate the heating performance of an electric vehicle heat pump air conditioning system at low temperature, an experimental platform for the air source heat pump air conditioning system was set up in this study to experimentally determine the heating performance of an electric vehicle heat pump air conditioning system with ambient temperature of ?10 ℃ to 0 ℃. The influences of the compressor speed (2 000–5 000 r/min), air inlet volume (300–400 m3/h), and ambient temperature on the performance of the system were analyzed. Finally, a formula was derived to estimate the range of the electric vehicle after using the air conditioning system. The results show that with an increase in compressor speed, the compressor discharge pressure and temperature, as well as the heat produced by the compressor, somewhat increase; however, the COP of the system decreases. When the compressor speed and ambient temperature are kept unchanged, the inlet air volume of the air conditioning box increases from 300 m3/h to 400 m3/h, heat production increases by 13.3%–26.0% and the COP increases by 0.03–0.80. Under other constant conditions, when the ambient temperature rises from ?10 ℃ to 0 ℃, the heat produced by the heat pump air-conditioning system increases by 60.9%–71.0% and the COP increases by 0.51–0.63. According to the formula, when the ambient temperature is ?10 ℃ to 0 ℃, the range of the heat pump air conditioning system can be improved by 13.5%–20.8% compared with the condition of same heating capacity, using a PTC heater.